Task modality and pair formation method: Their impact on patterns of interaction and LREs among EFL primary school children. (February 2019) - García Mayo, María del Pilar; Imaz Agirre, Ainara
Abstract: Research on L2 interaction among adults has shown that task modality influences language learning opportunities, with oral tasks eliciting more attention to meaning and tasks including a written component more attention to form. Recent research has also shown that pairing method has an impact on the nature of peer interaction. However, no research on these topics has been carried out with young learners in foreign language settings. This study examines the interaction of 32 dyads of 11–12 year-old Spanish EFL learners with an elementary proficiency level while they completed an oral task and an oral + written task. They were divided into proficiency-paired, teacher-selected and self-selected groups, whose interaction was video recorded, transcribed and analyzed for interactional patterns and frequency, nature and outcome of language-related episodes (LREs). The findings revealed that children were mostly collaborative in both modalities but there were differences regarding how the tasks unfolded. As for attention to form, the children generated more LREs in the oral + written task. The qualitative analysis showed that they pooled their linguistic resources together in order to correctly solve at least half of the LREs produced.